Creating mutant Murine Cytomegalovirus using signature tag mutagenesis - Phong, Vu Gia (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2023)
Cytomegalovirus (CMV) belongs to the Beta subclass of Herpes virus family. Human Cytomegalovirus (HCMV) was found to be ubiquitous in human populations. While remaining asymptomatic or only causing mild subclinical consequences in healthy populations, HCMV causes debilitating symptoms in individuals whose immune system is compromised such as blindness, pneumonia in AIDS patients, mental or behavioral dysfunction in neonates, and allograft rejections. To make matters worse, the virus will establish a life-long latent and persistent infection. Currently, there are no effective vaccine or treatment methods for the virus clinically. In addition, HCMV research is challenging because Beta Herpes virus infections are highly species-specific. To overcome this barrier presented by HCMV, researchers make use of Mouse Cytomegalovirus (MCMV) because MCMV shares a high degree of genetic similarity and disease manifestation with HCMV. In this study, Bacterial Artificial Chromosome techniques developed in the Liu Fenyong Lab - UC Berkeley is coupled with signature tag mutagenesis to generate deletion mutants for each of the 170 genes in pSM3fr - our MCMV BAC construct. Using our novel design, we successful generate tagged mutants and demonstrate that we can distinguish each separate tagged virus from one another.